Impact and prevention of errors in endovascular treatment of unruptured intracranial aneurysms. Issue 5 (October 2020) - Ospel, Johanna Maria; Kashani, Nima; Mayank, Arnuv; Cimflova, Petra; Heran, Manraj; Pandey, Sachin; Peeling, Lissa; Gopinathan, Anil; Lopes, Demetrius; Kocer, Naci; Goyal, Mayank
Background: Preventing errors and complications in neurointervention is crucial, particularly in the treatment of unruptured intracranial aneurysms (UIAs), where the natural history is generally benign, and the margin of treatment benefit small. We aimed to investigate how neurointerventionalists perceive the importance and frequency of errors and the resulting complications in endovascular UIA treatment, and which steps could be taken to prevent them. Methods: An international multidisciplinary survey was conducted among neurointerventionalists. Participants provided their demographic characteristics and neurointerventional treatment volume. They were asked about their perceptions on the importance and frequency of different errors in endovascular UIA treatment, and which solutions they thought to be most effective in preventing these errors. Results: Two-hundred-thirty-three neurointerventionalists from 38 countries participated in the survey. Participants identified errors in technical execution as the most common source of complications in endovascular UIA treatment (40.4% thought these errors constituted a relatively or very large proportion of all complication sources), closely followed by errors in decision-making/indication (32.2%) and errors related to management of unexpected events (28.4%). Simulation training was thought to be most effective in reducing technical errors, while cognitive errors were believed to be best minimized by abandoning challenging procedures, more honest discussion of complications and better standardization of procedure steps. Conclusion: Neurointerventionalists perceived both technical and cognitive errors to be important sources of complications in endovascular UIA treatment. Simulation training, a cultural change, higher acceptance of bail-out strategies and better standardization of procedures were perceived to be most effective in preventing these.